Consider this solution, if it is possible, check the result:
1) if to divide polynomial 'x³-3x²-6x+8' on 'x+2' result is: x²-5x+4, then x³-3x²-6x+8=(x+2)(x²-5x+4);
2) x²-5x+4=(x-1)(x-4), then
3) x³-3x²-6x+8=(x+2)(x-1)(x-4).
4) zeros are: -2;1;4. Other zeros are: 1 and 4.
Answer: 1;4.
The cost of meal = ![$30](https://tex.z-dn.net/?f=%2430)
The tip to the waiter =
%
Discount =
%
Cost = ![30 + 0.08 * 30 - 0.1 * 30](https://tex.z-dn.net/?f=30%20%2B%200.08%20%2A%2030%20-%200.1%20%2A%2030)
Cost = ![30(1 + 0.08 - 0.1)](https://tex.z-dn.net/?f=30%281%20%2B%200.08%20-%200.1%29)
Cost = $
0
Answer:
y = (1/2)x + 0
Step-by-step explanation:
The equation would be y = mx + b
m is the slope and b is the y-intercept
Answer:
x= -2 and y= 3
Step-by-step explanation:
since x = 2y -8, substitute this in the first equation
Thus, -3(2y-8) + 2y =12
-6y+24+2y=12
-6y+2y=12-24
-4y=-12
y=3
put the value of y in the second equation,
x=2y-8
x=2(3)-8
x=6-8
x=-2
So, x=-2. y=3